Determinants of violent crime in the U.S. evidence from state level data - Piggott, Grace (University of Wisconsin--Stout. Research Services, 2015)
This study examines the determinants of violent crime in the United States. It argues that violent crime is affected by socio-economic and public policy factors. To test the hypothesis, the study uses recent state level data on violent crime from FBI uniform crime reports. Fixed effect regression was used to analyze the data. The results indicated that there is a positive relationship between income inequality and crime. An increase in the level of inequality by one unit will result in an increase in violent crime by 330. We also found that control variables, such as state and local government expenditures on policing and public safety, and community development reduce violent crime. Other factors, such as education and population density are not statistically significant, showing they do not directly affect crime. These results help us better understand the determinants of violent crime and what must be done to reduce criminality in our society. First, there have to be policy measures to diminish the trend towards increased income inequality in order to reduce delinquency. Second, states have to continue dedicating adequate resources towards policing and public safety, and increase community development, in order to reduce crime.
Research article with tables and graphs.
Keywords: violent crime; Public safety; Violent crimes; Public policy